Effect of phytate and zinc ions on fluoride toothpaste efficacy using an in situ caries model. (June 2018) - Parkinson, Charles R.; Burnett, Gary R.; Creeth, Jonathan E.; Lynch, Richard J.M.; Budhawant, Chandrashekhar; Lippert, Frank; Hara, Anderson T.; Zero, Domenick T.
Abstract: Objectives: To compare and explore the dose-response of phytate-containing 1150 ppm fluoride toothpastes on model caries lesions and to determine the impact of zinc ions. Methods: This was a single-centre, randomised, blinded (examiner/laboratory analyst), six-treatment, four-period crossover, in situ study in adults with a removable bilateral maxillary partial denture. Study treatments were toothpastes containing: 0.425% phytate/F; 0.85% phytate/F; 0.85% phytate/Zn/F; F-only; Zn/F and a 0% F placebo. Where present, F was 1150 ppm as NaF; Zn was 0.3% as ZnCl2 . Human enamel specimens containing early-stage, surface-softened (A-lesions) or more advanced, subsurface (B-lesions) caries lesions were placed into the buccal flanges of participants' modified partial denture (one of each lesion type per side). A-lesions were removed after 14 days of twice-daily treatment use; B-lesions were removed after a further 14 days. A-lesions were analysed for surface microhardness recovery. Both lesion types were analysed by transverse microradiography and for enamel fluoride uptake, with B-lesions additionally analysed by quantitative light-induced fluorescence. Comparison was carried out using an analysis of covariance model. Results: Statistically significant differences between 1150 ppm F and the placebo toothpastes (p < 0.05) were shown for all measures, validating the model. No differences between fluoride toothpastes were observed for any measure with little evidence of a dose-response for phytate. Study treatments were generally well-tolerated. Conclusions: Results suggest phytate has little impact on fluoride's ability to promote early-stage lesion remineralisation or prevent more advanced lesion demineralisation in this in situ caries model. Similarly, results suggest zinc ions do not impair fluoride efficacy. Clinical significance: Toothpastes may contain therapeutic or cosmetic agents that could interfere with fluoride's caries prevention efficacy. The present in situ caries study has demonstrated that phytate, added to provide enhanced extrinsic stain removal/prevention, and zinc, added to inhibit malodour, do not impair fluoride efficacy.